Antistatic polyether-ether-ketone alloy material as well as preparation method and application thereof

By using carbon fiber, ceramic whiskers and calcium carbonate compound in antistatic polyether ether ketone alloy materials, combined with specific ratios of polyetherimide and polyphenylene sulfide, the decline in mechanical properties and high thermal expansion coefficient are solved. The problem has achieved efficient electrostatic dispersion, mechanical strengthening and thermal stability improvement.

CN119463453APending Publication Date: 2025-02-18GUANGDONG ZHONGCHENG SPECIAL MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411797863.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

After adding conductive fillers, the existing anti-static polyether ether ketone alloy materials have reduced mechanical properties, especially tensile strength, impact strength and fracture toughness, and have a large thermal expansion coefficient, which limits its application.

Method used

By combining carbon fiber, ceramic whiskers and calcium carbonate, a uniform and continuous conductive network is formed to improve the material's antistatic properties and notched impact strength. At the same time, a specific ratio of polyetherimide and polyphenylene sulfide are used to improve the thermal expansion coefficient of the material and the thermal deformation temperature at 1.8 MPa.

Benefits of technology

It significantly improves the overall conductivity of the material, improves the anti-static performance and notch impact strength, reduces the thermal expansion coefficient, and increases the thermal deformation temperature at 1.8MPa, ensuring that the material maintains good mechanical properties and dimensional stability in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005177248880000091
    Figure BDA0005177248880000091
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and particularly relates to an antistatic polyether-ether-ketone alloy material. The antistatic polyether-ether-ketone alloy material comprises the following components in parts by weight: 60-80 parts of modified polyether-ether-ketone, 10-20 parts of polyetherimide, 15-25 parts of polyphenylene sulfide, 3-9 parts of polytetrafluoroethylene, 5-10 parts of a plasticizer and 2-6 parts of a stabilizer, the preparation method of the modified polyether-ether-ketone comprises the following steps: mixing carbon fibers, ceramic whiskers and calcium carbonate to form a mixed material, adding 15-20 parts by weight of the mixed material and 2-4 parts by weight of a silane coupling agent KH550 into a high-speed mixer, and mixing for 5-15 minutes; and continuously adding 80 parts by weight of polyether-ether-ketone into the high-speed mixer, mixing for 5-10 minutes, and then extruding and granulating in a double-screw extruder. The prepared polyether-ether-ketone alloy material is good in antistatic effect, excellent in mechanical property and wide in application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to an antistatic polyetheretherketone alloy material and a preparation method and application thereof. Background Art

[0002] As a high-performance semi-crystalline thermoplastic engineering plastic, polyetheretherketone (PEEK) is widely used in the automotive industry due to its excellent mechanical properties, high temperature resistance, self-lubrication, chemical resistance, flame retardancy and radiation resistance. The electrical and electronic systems in automobiles (such as engine control units, sensors, wiring harnesses, etc.) are very sensitive to static electricity. Electrostatic discharge may damage electronic components and cause system failure. Therefore, using antistatic PEEK materials to manufacture connectors and sockets can effectively prevent static electricity accumulation and protect the safety and reliability of electronic equipment.

[0003] In order to give PEEK materials antistatic properties, they can usually be modified in the following ways: (1) Adding conductive fillers: such as carbon fiber, carbon black, metal powder, etc. These fillers can improve the conductivity of the material and effectively disperse static electricity. (2) Surface coating: Applying a layer of conductive coating on the surface of PEEK material can achieve antistatic effect without changing the properties of the material itself. (3) Blending modification: PEEK is blended with other polymers with good conductivity to form a composite material, which can not only maintain the excellent properties of PEEK but also improve its antistatic ability. However, the addition of conductive fillers may cause the mechanical properties of PEEK materials to decrease, especially tensile strength, impact strength and fracture toughness. This is because the presence of conductive fillers may destroy the continuity of the PEEK matrix, forming stress concentration points, making the material more prone to crack propagation when subjected to stress. At the same time, the glass transition temperature Tg of PEEK material is relatively low, which limits its application.

[0004] Therefore, there is an urgent need for antistatic polyetheretherketone alloy materials and preparation methods and applications thereof. Summary of the invention

[0005] The purpose of the present invention is to provide an antistatic polyetheretherketone alloy material and a preparation method and application thereof.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The antistatic polyetheretherketone alloy material comprises the following components in parts by weight: 60-80 parts of modified polyetheretherketone, 10-20 parts of polyetherimide, 15-25 parts of polyphenylene sulfide, 3-9 parts of polytetrafluoroethylene, 5-10 parts of plasticizer, and 2-6 parts of stabilizer;

[0008] Furthermore, the preparation method of the modified polyetheretherketone comprises the following steps: mixing carbon fiber, ceramic whisker and calcium carbonate to form a mixed material, adding 15-20 parts by weight of the mixed material and 2-4 parts by weight of silane coupling agent KH550 into a high-speed mixer, and mixing for 5-15 minutes; continuing to add 80 parts by weight of polyetheretherketone into the high-speed mixer, mixing for 5-10 minutes, and then extruding in a twin-screw extruder for granulation.

[0009] Furthermore, the weight ratio of the carbon fiber, ceramic whisker and calcium carbonate is 1:(1.3-1.5):(0.3-0.7).

[0010] The electrical and electronic systems in automobiles (such as engine control units, sensors, wiring harnesses, etc.) are very sensitive to static electricity. In the prior art, carbon fiber is usually added to improve the antistatic property of polyetheretherketone alloy materials, but it is not ideal. The present invention selects carbon fiber, ceramic whiskers and calcium carbonate for compounding and improving, which can not only well improve the antistatic property, but also improve the notched impact strength of the material. When carbon fiber, ceramic whiskers and calcium carbonate coexist in the PEEK matrix, they can form a more uniform and continuous conductive network. Carbon fiber, as the main conductive filler, provides a high conductivity path; while ceramic whiskers and calcium carbonate play a "bridge" role, connecting the gaps between carbon fibers to form a more complete conductive path. This multiphase synergistic effect significantly improves the overall conductivity of the material and effectively disperses and conducts static electricity. Carbon fiber, ceramic whiskers and calcium carbonate form a complex multiphase composite system in the PEEK matrix, forming a synergistic effect of multiphase composite materials. These fillers not only have excellent mechanical properties each, but also can interact with each other to form a good interface bonding. This interfacial bonding helps to transfer external forces to the filler more effectively, disperse stress, and reduce stress concentration points in the matrix, thereby improving the overall toughness and impact strength of the material.

[0011] Furthermore, the diameter of the single fiber of the carbon fiber is 7 μm, and the aspect ratio is 2:1 to 8:1. It is purchased from Shenzhen Turing New Materials Co., Ltd. The ceramic whisker is purchased from Shanghai Gerunya Nanomaterials Co., Ltd., 1-3 μm. The particle size of calcium carbonate is 50-60 nm, purchased from Shanghai Gerunya Nanomaterials Co., Ltd.

[0012] Furthermore, the extrusion temperature of the twin-screw extruder is 380-390°C.

[0013] Further, the polyetherimide includes polyetherimide I of model E2200, polyetherimide II of model 3150 and polyetherimide III of model E2200L3 in a weight ratio of 1: (1.2-1.4): (0.5-0.7), all of which are purchased from Dongguan Hongwen Plastic Chemical Co., Ltd.

[0014] Furthermore, the polyphenylene sulfide includes polyphenylene sulfide I of model B4300GM82, polyphenylene sulfide II of model B5200C6 and polyphenylene sulfide III of model B4100ST2 in a weight ratio of (1.5-1.7):(0.3-0.5):1, all of which are purchased from Jiangsu Ourida New Material Technology Co., Ltd.

[0015] Polyetheretherketone alloy materials on the market usually add polyphenylene sulfone (PPS). PPS is a non-crystalline polymer with a small shrinkage rate, while PEEK is a semi-crystalline polymer with a large shrinkage rate. By adding PPS, the shrinkage rate of PEEK can be effectively reduced, the dimensional accuracy can be improved, and the deformation problem after molding can be reduced. However, although the addition of PPS can improve certain mechanical properties (such as toughness), it may also cause the tensile strength and hardness of PEEK to decrease. This is because the strength and hardness of PPS are relatively low. At the same time, although PPS has good short-term heat resistance, its performance may gradually decrease under long-term high temperature environments. This may shorten the service life of PEEK / PPS alloy materials at high temperatures, especially in environments with continuous high temperatures or repeated heating and cooling, where the thermal expansion coefficient is large. The present invention attempts to use polyetherimide and polyphenylene sulfide to improve the thermal expansion coefficient of polyetheretherketone alloy materials, but the effect is not ideal. Through a large number of experiments, it was found that the use of polyetherimide and polyphenylene sulfide compounded in a specific ratio in the system of the present invention can improve the thermal expansion coefficient of polyetheretherketone alloy materials.

[0016] Furthermore, the weight ratio of the modified polyetheretherketone, polyetherimide and polyphenylene sulfide is (65-70):(12-17):(18-22).

[0017] The heat deformation temperature (HDT) of polyetheretherketone (PEEK) alloy material at 1.8MPa is a very important performance indicator, which reflects the heat resistance of the material under stress conditions. HDT is a key indicator to measure the material's ability to maintain shape and structural integrity under high temperature conditions. For PEEK alloy materials, HDT at 1.8MPa can be used to determine its maximum operating temperature when subjected to a certain load. In the experiment, it was found that when modified polyetheretherketone, polyetherimide and polyphenylene sulfide are mixed in a specific proportion, the heat deformation temperature of polyetheretherketone alloy material at 1.8MPa can be improved. The three components can improve the heat deformation temperature of polyetheretherketone alloy material at 1.8MPa through synergistic effect.

[0018] Polytetrafluoroethylene, brand: Asahi Glass, model: PTFE L169J.

[0019] Furthermore, the plasticizer is dibutyl phthalate. Fuyida Chemical (Shandong) Co., Ltd.

[0020] Furthermore, the stabilizer is di-tert-butyl-p-cresol.

[0021] The second aspect of the present invention provides a method for preparing an antistatic polyetheretherketone alloy material, comprising the following steps: stirring the components of the antistatic polyetheretherketone alloy material in a high-speed stirrer for 10-15 minutes to mix them evenly; putting them into a twin-screw extruder, extruding and granulating them at a temperature of 390-400°C, cooling and granulating, and drying to obtain the antistatic polyetheretherketone alloy material.

[0022] Furthermore, during the extrusion granulation, the screw speed of the twin-screw extruder is 20-40 r / min.

[0023] The invention also provides application of the antistatic polyetheretherketone alloy material in preparing automotive electrical and electronic systems.

[0024] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0025] 1. The present invention selects carbon fiber, ceramic whisker and calcium carbonate for compounding to improve not only the antistatic property, but also the notched impact strength of the material.

[0026] 2. The present invention can improve the thermal expansion coefficient of polyetheretherketone alloy material by using polyetherimide and polyphenylene sulfide compounded in a specific ratio.

[0027] 3. In the system of the present invention, when the modified polyetheretherketone, polyetherimide and polyphenylene sulfide are mixed in a specific ratio, the heat deformation temperature of the polyetheretherketone alloy material at 1.8 MPa can be improved. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] This embodiment provides an antistatic polyetheretherketone alloy material, comprising the following components in parts by weight: 68 parts of modified polyetheretherketone, 15 parts of polyetherimide, 20 parts of polyphenylene sulfide, 5 parts of polytetrafluoroethylene, 7 parts of plasticizer, and 4 parts of stabilizer;

[0031] The polytetrafluoroethylene is of the brand Asahi Glass of Japan, model PTFE L169J. The plasticizer is dibutyl phthalate, produced by Fuyida Chemical (Shandong) Co., Ltd. The stabilizer is di-tert-butyl-p-cresol.

[0032] The preparation method of the modified polyetheretherketone comprises the following steps: mixing carbon fiber, ceramic whisker and calcium carbonate in a weight ratio of 1:1.4:0.5 to form a mixed material, adding 18 parts by weight of the mixed material and 3 parts by weight of silane coupling agent KH550 into a high-speed mixer, and mixing for 10 minutes; continuously adding 80 parts by weight of polyetheretherketone into the high-speed mixer, mixing for 7 minutes, and then extruding in a twin-screw extruder, the extrusion temperature of the twin-screw extruder is 385°C, and granulating.

[0033] The diameter of the carbon fiber single filament is 7 μm, the aspect ratio is 2:1-8:1, and it is purchased from Shenzhen Turing New Materials Co., Ltd. The ceramic whisker is purchased from Shanghai Green Asia Nano Materials Co., Ltd., 1-3 μm. The particle size of calcium carbonate is 50-60 nm, and it is purchased from Shanghai Green Asia Nano Materials Co., Ltd.

[0034] The polyetherimide includes polyetherimide I of model E2200, polyetherimide II of model 3150 and polyetherimide III of model E2200L3 in a weight ratio of 1:1.3:0.6, all of which are purchased from Dongguan Hongwen Plastic Chemical Co., Ltd.

[0035] The polyphenylene sulfide includes polyphenylene sulfide I of model B4300GM82, polyphenylene sulfide II of model B5200C6 and polyphenylene sulfide III of model B4100ST2 in a weight ratio of 1.6:0.4:1, all of which are purchased from Jiangsu Ourida New Material Technology Co., Ltd.

[0036] The preparation method of the antistatic polyetheretherketone alloy material comprises the following steps: stirring the components of the antistatic polyetheretherketone alloy material in a high-speed stirrer for 12 minutes to mix them evenly; putting them into a twin-screw extruder, extruding and granulating them at a temperature of 395°C, the screw speed of the twin-screw extruder is 30r / min, cooling, granulating and drying to obtain the antistatic polyetheretherketone alloy material.

[0037] Example 2

[0038] This embodiment provides an antistatic polyetheretherketone alloy material, comprising the following components in parts by weight: 65 parts of modified polyetheretherketone, 12 parts of polyetherimide, 22 parts of polyphenylene sulfide, 9 parts of polytetrafluoroethylene, 5 parts of plasticizer, and 6 parts of stabilizer;

[0039] The polytetrafluoroethylene is of the brand Asahi Glass of Japan, model PTFE L169J. The plasticizer is dibutyl phthalate. Fuyida Chemical (Shandong) Co., Ltd. The stabilizer is di-tert-butyl-p-cresol.

[0040] The preparation method of the modified polyetheretherketone comprises the following steps: mixing carbon fiber, ceramic whisker and calcium carbonate in a weight ratio of 1:1.3:0.7 to form a mixed material, adding 15 parts by weight of the mixed material and 4 parts by weight of a silane coupling agent KH550 into a high-speed mixer, and mixing for 15 minutes; continuously adding 80 parts by weight of polyetheretherketone into the high-speed mixer, mixing for 5 minutes, and then extruding in a twin-screw extruder at an extrusion temperature of 390°C, and granulating.

[0041] The diameter of the single fiber of carbon fiber is 7 μm, and the aspect ratio is 2:1 to 8:1. It was purchased from Shenzhen Turing New Materials Co., Ltd. The ceramic whiskers were purchased from Shanghai Green Asia Nano Materials Co., Ltd., 1-3 μm. The particle size of calcium carbonate is 50-60 nm, purchased from Shanghai Green Asia Nano Materials Co., Ltd.

[0042] The polyetherimide includes polyetherimide I of model E2200, polyetherimide II of model 3150 and polyetherimide III of model E2200L3 in a weight ratio of 1:1.2:0.7, all of which are purchased from Dongguan Hongwen Plastic Chemical Co., Ltd.

[0043] The polyphenylene sulfide includes polyphenylene sulfide I of model B4300GM82, polyphenylene sulfide II of model B5200C6 and polyphenylene sulfide III of model B4100ST2 in a weight ratio of 1.5:0.5:1, all of which are purchased from Jiangsu Ourida New Material Technology Co., Ltd.

[0044] The preparation method of the antistatic polyetheretherketone alloy material comprises the following steps: stirring the components of the antistatic polyetheretherketone alloy material in a high-speed stirrer for 15 minutes to mix them evenly; putting them into a twin-screw extruder, extruding and granulating them at a temperature of 390°C, the screw speed of the twin-screw extruder is 40r / min, cooling, granulating and drying to obtain the antistatic polyetheretherketone alloy material.

[0045] Comparative Example 1

[0046] The difference between this comparative example and Example 1 is that the preparation method of the modified polyetheretherketone comprises the following steps: adding 18 parts by weight of carbon fiber and 3 parts by weight of silane coupling agent KH550 into a high-speed mixer and mixing for 10 minutes; continuing to add 80 parts by weight of polyetheretherketone into the high-speed mixer and mixing for 7 minutes, and then extruding in a twin-screw extruder with an extrusion temperature of 385°C and granulating.

[0047] The carbon fiber single filament has a diameter of 7 μm and an aspect ratio of 2:1 to 8:1 and was purchased from Shenzhen Turing New Materials Co., Ltd.

[0048] Comparative Example 2

[0049] The difference between this comparative example and Example 1 is that carbon fibers, ceramic whiskers and calcium carbonate are mixed in a weight ratio of 1:1:1 to form a mixed material.

[0050] The diameter of the single fiber of carbon fiber is 7 μm, and the aspect ratio is 2:1 to 8:1. It was purchased from Shenzhen Turing New Materials Co., Ltd. The ceramic whiskers were purchased from Shanghai Green Asia Nano Materials Co., Ltd., 1-3 μm. The particle size of calcium carbonate is 50-60 nm, purchased from Shanghai Green Asia Nano Materials Co., Ltd.

[0051] Comparative Example 3

[0052] The difference between this comparative example and Example 1 is that the polyetherimide is polyetherimide of model E2200 purchased from Dongguan Hongwen Plastic Chemical Co., Ltd.

[0053] Comparative Example 4

[0054] The difference between this comparative example and Example 1 is that the polyetherimide comprises polyetherimide I of model E2200, polyetherimide II of model 3150 and polyetherimide III of model E2200L3 in a weight ratio of 1:1:1, all of which are purchased from Dongguan Hongwen Plastic Chemical Co., Ltd.

[0055] Comparative Example 5

[0056] The difference between this comparative example and Example 1 is that the polyphenylene sulfide is polyphenylene sulfide of model B4300GM82, which is purchased from Jiangsu Ourida New Material Technology Co., Ltd.

[0057] Comparative Example 6

[0058] The difference between this comparative example and Example 1 is that the polyphenylene sulfide includes polyphenylene sulfide I of model B4300GM82, polyphenylene sulfide II of model B5200C6 and polyphenylene sulfide III of model B4100ST2 in a weight ratio of 1:1:1, all of which are purchased from Jiangsu Ourida New Material Technology Co., Ltd.

[0059] Comparative Example 7

[0060] The difference between this comparative example and Example 1 is that the antistatic polyetheretherketone alloy material includes the following components in parts by weight: 60 parts of modified polyetheretherketone, 28 parts of polyetherimide, 15 parts of polyphenylene sulfide, 5 parts of polytetrafluoroethylene, 7 parts of plasticizer, and 4 parts of stabilizer.

[0061] Performance Testing

[0062] The antistatic polyetheretherketone alloy materials prepared in Examples 1-2 and Comparative Examples 1-7 were subjected to the following performance tests:

[0063] Tensile strength 5mm / min: ASTM D638;

[0064] Elongation at break 5mm / min: ASTM D638;

[0065] Notched impact strength: ASTM D256;

[0066] Heat deformation temperature at 1.8MPa: ISO 75-2 / A;

[0067] Coefficient of thermal expansion, (>150°C): ASTM E831;

[0068] The results are shown in Table 1.

[0069] Table 1 Performance test results

[0070]

[0071] From the above performance test results, it can be seen that the antistatic polyetheretherketone alloy materials of Examples 1-2 have excellent comprehensive performance, especially the comprehensive performance of Example 1 is the most outstanding, which is mainly due to the synergistic effect between the components. The thermal expansion coefficient of the antistatic polyetheretherketone alloy material of the present invention is less than 4×10 -5 *1 / k; The heat deformation temperature is greater than 200℃ at 1.8MPa. The electrical and electronic systems of automobiles are usually located in the engine compartment or other high-temperature areas, where the temperature may be as high as 150-200℃ or even higher. The HDT of PEEK alloy material is greater than 200℃, which means that it can maintain good mechanical properties and dimensional stability under these extreme temperature conditions, and will not soften, deform or fail due to high temperature. This ensures that key components (such as engine control units, sensors, wiring harnesses, etc.) can still work normally in high temperature environments, avoiding system failures caused by material failure. High temperature environments will accelerate the aging and performance degradation of materials, especially under long-term exposure. The high HDT of PEEK alloy material indicates that it has excellent long-term heat resistance, can maintain stable performance in high temperature environments, extend the service life of electrical and electronic systems, and reduce maintenance and replacement frequency. The heat deformation temperature of polyetheretherketone (PEEK) alloy material is greater than 200℃ at 1.8MPa. This performance indicator is of great significance for electrical and electronic systems in automobiles (such as engine control units, sensors, wiring harnesses, etc.). It not only ensures the structural stability and reliability of these systems in high temperature environments, but also improves the safety and long-term performance of the system, meeting strict industry standards and regulatory requirements. In addition, the high HDT of PEEK alloy materials also provides designers with more flexibility, supports lightweight design and cost optimization, and enhances the market competitiveness of products.

[0072] However, the comparative examples are significantly inferior to the embodiments in the corresponding performance tests because they do not adopt the necessary technical solutions. In comparative example 1, only carbon fiber is used to modify polyetheretherketone, and the ratio of carbon fiber, ceramic whisker and calcium carbonate in comparative example 2 is different, and the antistatic property and notched impact strength are reduced. The compositions of polyetherimide in comparative examples 3 and 4 are different, and the compositions of polyphenylene sulfide in comparative examples 5 and 6 are different, and the thermal expansion coefficient of polyetheretherketone alloy material increases. In comparative example 7, the ratios of modified polyetheretherketone, polyetherimide and polyphenylene sulfide are different, and the heat deformation temperature of polyetheretherketone alloy material under 1.8MPa decreases. The above experimental results further demonstrate the importance of the technical solution defined in the present invention for its technical effect.

[0073] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. Antistatic polyetheretherketone alloy material, characterized in that: The invention comprises the following components in parts by weight: 60-80 parts of modified polyetheretherketone, 10-20 parts of polyetherimide, 15-25 parts of polyphenylene sulfide, 3-9 parts of polytetrafluoroethylene, 5-10 parts of plasticizer and 2-6 parts of stabilizer; The preparation method of the modified polyetheretherketone comprises the following steps: mixing carbon fiber, ceramic whisker and calcium carbonate to form a mixed material; adding 15-20 parts by weight of the mixed material and 2-4 parts by weight of silane coupling agent KH550 into a high-speed mixer and mixing for 5-15 minutes; continuously adding 80 parts by weight of polyetheretherketone into the high-speed mixer and mixing for 5-10 minutes, and then extruding in a twin-screw extruder and granulating.

2. The antistatic polyetheretherketone alloy material according to claim 1, characterized in that: The weight ratio of the carbon fiber, the ceramic whisker and the calcium carbonate is 1:(1.3-1.5):(0.3-0.7).

3. The antistatic polyetheretherketone alloy material according to claim 1, characterized in that: The extrusion temperature of the twin-screw extruder is 380-390°C.

4. The antistatic polyetheretherketone alloy material according to claim 1, characterized in that: The polyetherimide includes polyetherimide I of model E2200, polyetherimide II of model 3150 and polyetherimide III of model E2200L3 in a weight ratio of 1:(1.2-1.4):(0.5-0.7).

5. The antistatic polyetheretherketone alloy material according to claim 4, characterized in that: The polyphenylene sulfide includes polyphenylene sulfide I of model B4300GM82, polyphenylene sulfide II of model B5200C6 and polyphenylene sulfide III of model B4100ST2 in a weight ratio of (1.5-1.7):(0.3-0.5):

1.

6. The antistatic polyetheretherketone alloy material according to claim 5, characterized in that: The weight ratio of the modified polyetheretherketone, polyetherimide and polyphenylene sulfide is (65-70):(12-17):(18-22).

7. The antistatic polyetheretherketone alloy material according to claim 1, characterized in that: The plasticizer is dibutyl phthalate.

8. The antistatic polyetheretherketone alloy material according to claim 1, characterized in that: The stabilizer is di-tert-butyl-p-cresol.

9. A method for preparing the antistatic polyetheretherketone alloy material according to any one of claims 1 to 8, characterized in that: The following steps are involved: The components of the antistatic polyetheretherketone alloy material are stirred in a high-speed stirrer for 10-15 minutes to be uniformly mixed; the components are put into a twin-screw extruder, extruded and granulated at a temperature of 390-400° C., cooled, pelletized and dried to obtain the antistatic polyetheretherketone alloy material.

10. Use of the antistatic polyetheretherketone alloy material according to any one of claims 1 to 8 in the preparation of automotive electrical and electronic systems.